Proceedings of the Fourth Conference on Machine Translation (Volume 2: Shared Task Papers, Day 1) 2019
DOI: 10.18653/v1/w19-5340
|View full text |Cite
|
Sign up to set email alerts
|

CUED@WMT19:EWC&LMs

Abstract: Two techniques provide the fabric of the Cambridge University Engineering Department's (CUED) entry to the WMT19 evaluation campaign: elastic weight consolidation (EWC) and different forms of language modelling (LMs). We report substantial gains by finetuning very strong baselines on former WMT test sets using a combination of checkpoint averaging and EWC. A sentence-level Transformer LM and a document-level LM based on a modified Transformer architecture yield further gains. As in previous years, we also extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Recently, it was shown that the shallow fusion approach for sentencelevel NMT can be improved by compensating for the implicitly learned internal language model of the NMT system . Regarding the integration of a document-level LM, earlier approaches simply use the LM for re-ranking the hypothesis of the sentence-level NMT model (Stahlberg et al, 2019;Yu et al, 2020). Several works have proposed to employ a log-linear combination between sentence-level NMT system and document-level LM (Garcia et al, 2019;Jean and Cho, 2020;Sugiyama and Yoshinaga, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Recently, it was shown that the shallow fusion approach for sentencelevel NMT can be improved by compensating for the implicitly learned internal language model of the NMT system . Regarding the integration of a document-level LM, earlier approaches simply use the LM for re-ranking the hypothesis of the sentence-level NMT model (Stahlberg et al, 2019;Yu et al, 2020). Several works have proposed to employ a log-linear combination between sentence-level NMT system and document-level LM (Garcia et al, 2019;Jean and Cho, 2020;Sugiyama and Yoshinaga, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Beam search appears to be more exact, but there is no assurance that it will always lead to an interpretation with a higher or comparable score than greedy decoding. [38] According to Stahlberg and Byrne (2019), beam search has a huge number of searching errors.…”
Section: A Greedy and Beam Searchmentioning
confidence: 99%
“…Stahlberg et al. (2018),[38]Stahlberg and Byrne,[40]Niehues et al (2017), [41][42]Stahlberg et al (2018), and (2019). In particular,[38]Stahlberg and Byrne (2019) showed that the NMT decoding had a substantial number of search mistakes.…”
mentioning
confidence: 99%
“…The Cambridge University Engineering Department's system [101] relied on document-level language models to improve the sentence-level NMT system. They modified the Transformer architecture for document-level language modelling by introducing separate attention layers for inter-and intra-sentential context.…”
Section: Shared Tasks In Wmt19 and Wngt19mentioning
confidence: 99%